Smartphone use and dependence among adolescents attending full-time school setting (Research, Society and Development, 2021)
Objectives: To know the profile of smartphone use and dependence of adolescents in full-time schools. Method: Cross-sectional study carried out in six State Schools of Professional Education (EEEP) in the city of Fortaleza, Ceará, Brazil, developed between September and October 2019. 286 adolescents (15-19 years old) participated who answered two questionnaires (sociodemographic data, use and smartphone dependency). SPSS 23.0 was used for descriptive and inferential analysis, with the outcome being smartphone dependence. Results: There was a higher percentage of males (53.5%), age of 16 years (31.5%) and social class D (52.4%). Regarding usage, 96.2% used to access social networks, 71.0% to receive and make calls, 68.9% to play games and 66.1% to watch movies. It was found that 62.6% had smartphone dependence, with 7.3 (± 3.4) hours / daily use time. An association was found between smartphone dependence and age (OR: 1.48; p=0.009), using headphones (OR: 2.76; p